31.6k views
2 votes
G(x) = -4x-1 f(x) = 2x^3 + 5x^2 Find (gof)(0)

1 Answer

2 votes

gof mean g (f(x))

f(x) = 2x^3 +5x^2

g(x) = - 4x - 1

so g(f(x)) is , put x = value of f(x) in g(x)

gof(x) = - 4*(2x^3 +5x^2) - 1

gof(x) = -8x^3 - 20 x^2 - 1

for gof(0), put x = 0 in the above expression

gof(0) = - 8* 0^3 -20 0^2 - 1

gof(0) = 0 - 0 - 1

gof(0) = -1

so the answer is gof(0) = -1

User Rajeemcariazo
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.